Shehu Musa Yar'adua: Neither North nor South, East nor West: One Nigeria - Farris, Jacqueline (Shehu Musa Yar' Adua Foundation)
A Children Story which tells a compelling story not only of Late Tafidan Katsina but also of an important period in Nigeria history through the eyes of a child.
Keywords: Juvenile Non-Fiction / Biography-Shehu Musa Yar'Adua